Spontaneous heterotopic pregnancy with tubal rupture - J. C., Spandana; S. Kanakannavar, Suresh; K. M., Umashankar; N., Manuja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Heterotopic pregnancy is the coexistence of intrauterine pregnancy (IUP) and extrauterine gestation. It is a rare and dangerous life-threatening condition that is difficult to diagnose and easily missed. The incidence in the general population is estimated to be 1 in 30,000. We report a case of a 24-year-old multigravida who was seen in the emergency department with a diagnosis of a ruptured ectopic pregnancy. A careful ultrasound assessment led to the diagnosis of a heterotopic pregnancy despite lack of any notable risk factors. Immediate surgical intervention with supportive measures resulted in a successful outcome. An obstetrician should keep in mind the occurrence of a heterotopic pregnancy while dealing with pregnant females. It also demonstrates that early diagnosis is essential in order to salvage the intrauterine pregnancy and avoid maternal morbidity and mortality.